Predatory Gall Midge (unofficial common name), Feltiella acarisuga (Vallot) (Insecta: Diptera: Cecidomyiidae) - Ryan S. Osborne; Norman C. Leppla; Lance S. Osborne (EDIS)
The predatory gall midge, Feltiella acarisuga (Vallot), is one of the most effective and widespread natural enemies of spider mites (Tetranychidae) (Gagne 1995). It is a particularly important natural enemy of the twospotted spider mite, Tetranychus urticae Koch, in a number of cropping systems (Opit et al. 1997). F. acarisuga could be particularly useful for integrated pest management of spider mites that attack greenhouse crops (Gillespie et al. 1998). This document is EENY-269, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2002.